GENERAL AND SPECIFIC FEATURES OF THE GEOGRAPHICAL LOCATION OF THE OKCHADARYA BASIN AND THE LOWER ZARAFSHAN VALLEY - Usmanova, I.I. (SCIENCE and SOCIETY, 2025)
This article examines the geographical location, natural conditions, and historical-geological processes of the Okchadarya Basin and the Lower Zarafshan Valley. The study analyzes the paleogeographic formation, climate changes, and anthropogenic impacts within the Turan Lowland.
Keywords: Shorokhan; Sultan Uvays; Kyzylkum and Aral; Akchadarya region; A.V. Vinogradov; Jonbos, Jonbos, 5, 11,12,14; Floor-7; Maʼmur -1, 3, 4, 3 B, 4; Kunek-1,3; Dingilji-6; Kurgoshin G, D; Tadzhiqazgan-2, 3, 6, 6 a, 10